Sejarah Koepang Di Bawah Pemerintahan Residen Jacob Arnoldus Hazaart Pada Tahun 1807-1832 - saefatu, fridiater; Djakariah, Djakariah; Ndoen, Fransina A (FLORESIENSIS, 2023)
This study aims to find out (1) How was the history of the Kupang government under Resident Jacob Arnoldus Hazaart in 1807-1810, 1814, 1819-1832, (2) How was the development of Kupang in the political, social, cultural and economic fields under the government of Resident Jacob Arnoldus Hazaart in 1807-1810, 1814, 1819-1832. This study is a historical analysis carried out with the steps of determining the topic, heuristics, source criticism, interpretation and historiography. The results of the study show, (1) Jacob Arnoldus Hazaart ruled as a resident in Kupang for three periods, namely from 1807-1810, 1814, 1819-1832. In 1810 the Dutch placed Jacob Arnoldus Hazaart as a resident in the Kupang region, (2) The development of Kupang in the political field, during the British occupation of Kupang (1812-1816) even though the region was under British control. Hazaart maintained the Dutch administration and played an important role in maintaining the stability of the government in the Kupang region, in the social field, the native people in Kupang were Helong, they interacted with other tribes in Kupang during the reign of the Hazaart resident.